The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

Interrogation proceedings in insolvency law: a comparative study - Mwelase, Musamuni Barrah (North-West University, 2019)
Interrogation proceedings in insolvency circumstances have always been a thorny issue in South Africa, even prior to the advent of the new constitutional democracy. After the adoption of the new Constitution in 1993, a number of court cases seeking adjudication on constitutional compliance came before our courts. The insolvency of both natural and juristic persons necessitates the employment of specified proceedings such as insolvency interrogations. The latter is done to enable an efficient and effective collection and collation of information that would assist in the administration, sequestration and winding-up of the affairs of the affected person. These proceedings are intended to benefit creditors of an insolvent (natural and juristic). The matters of Ferreira v Levin; Vryenhoek v Powell 1996 (1) SA 984 (CC) (1996) (1); Bernstein and Others v Bester 1996 (2) SA 751 (CC); Harksen v Lane 1998 (1) SA 300 (CC; De Lange v Smuts 1998 (1) SA 736 (C) are still leading cases in relation to the constitutionality of interrogations in insolvency circumstances. The Constitutional Court has on a number of occasions, declared the interrogation proceedings in insolvency matters constitutional, with minor amendments on a case-by-case basis. The effect of these judgements is that, in every case in which an insolvent debtor has to undergo an interrogation process, the presiding officer must ensure that compliance with the constitutional requirements are in place. The current position in which the sequestration of insolvent estates and the winding-up of insolvent companies are respectively regulated by two statutes, is a matter for concern. This situation has led to duplication and contradictions in the two statutes. Further, the absence of specialist tribunals or officers dedicated to the administration of insolvency related matters is a further hurdle to the effective and efficient finalisation of the affairs of insolvent estates or insolvent companies’ affairs. The matter of Leong comes to mind. In this case, the Master of the High Court issued a warrant of arrest for a witness who was subpoenaed to appear at the meeting of creditors in his insolvent estate. This was the case, despite the fact that Leong had previously submitted a medical certificate to the effect that he was unable to attend the meeting due to illness. This case is a clear indication of a lack of proper guidelines to deal with insolvency related matters - for non-judicial officers (such as the Master of the High Court). This incident took place in 2016, long after the decision in De Lange v Smuts 1998 (1) SA 736 (CC). Interrogation processes in insolvency circumstances in Namibia and Botswana are almost similar to South Africa’s processes. Divergent provisions in Namibia and Botswana exist, but not to a great extent. Like South Africa, the above-mentioned jurisdictions adopted a constitutional democracy long before South Africa. One would have expected that interrogation proceedings in insolvency circumstances would be in line with human rights. Further, as is the case in South Africa, insolvency of natural persons and of juristic persons are regulated by two separate statutes in these jurisdictions. This thesis investigates issues relating to the interrogation process in insolvency proceedings in the three SADC countries, namely South Africa, Namibia and Botswana. It compares the position to two foreign jurisdictions, namely England and Canada – as leading jurisdictions in human rights. Thereafter, suggestions on processes and methods of information gathering in line with human rights and in specialist tribunals will be made. In addition, recommendations for inclusion in a unified statute regulating insolvencies of both natural and juristic persons will be made. This will be done taking into consideration the economical and socio-political circumstances of South Africa and the SADC countries forming part of this thesis.
Keywords: Insolvency; Private enquiries; Public enquiries; Subpoena; Summons; UNCITRAL Model Law; World Bank

Aspects of the regulation of cross-border insolvency in South Africa - Chitimira, Howard (Obiter, 2018)
This article analyses the regulation of cross-border insolvency under the Cross-Border Insolvency Act 42 of 20001 in order to examine the adequacy of such regulation as regards to the enforcement of insolvency proceedings in South Africa and other relevant jurisdictions. To this end, the paper provides an overview analysis of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act. Moreover, where possible, the paper also provides a comparative analysis of selected aspects of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act and those that are provided under the Insolvency Act 24 of 1936 and other related international instruments. This is done to expose the challenges and future prospects of the regulatory and enforcement framework under the Cross-Border Insolvency Act in South Africa.
Keywords: Insolvency; Regulation; South Africa

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

United States' bankruptcy jurisdiction over foreign entities: exorbitant or congruent - Walters, Adrian J. (The Journal of Corporate Law Studies, 2017)
Alarmed at the ease with which global bankruptcy jurisdiction can be engineered in the US through a combination of the Bankruptcy Code’s low bar to entry and the worldwide effects of a bankruptcy case, critics argue that the US promotes abusive bankruptcy forum shopping and harmful imposition of US norms on overseas stakeholders. This article advances a revised account of US bankruptcy jurisdiction over non-US debtors from a distinctively Anglo-American standpoint. The article’s central thesis is that critics overemphasise formal jurisdictional rules and pay insufficient attention to how US courts actually exercise jurisdiction in practice. It compares the formal law ‘on the books’ in the US and UK for determining whether or not a domestic insolvency or restructuring proceeding relating to a foreign debtor can be maintained in each jurisdiction and provides a functional account of how US bankruptcy jurisdiction over foreign entities is exercised in practice using the concept of jurisdictional congruence as a benchmark.

Creditors' rights in business rescue proceedings in terms of South Africa's Companies Act 71 of 2008 - Rugumamu, Victor William (University of KwaZulu-Natal, 2017)
The focus of this study is the protection of creditors’ rights in South Africa’s statutory business rescue regime provided for in Chapter 6 of the Companies Act 71 of 2008. In this analysis, three issues in particular are addressed in depth. The first is the creditors` power to initiate the business rescue process. The second is the position of creditors between the commencement and the termination of the business rescue process. The third issue is to suggest (on the basis of experience drawn from reported case law and academic criticism of the current business rescue statutory provisions) an improved model that will more effectively safeguard creditors’ rights in South Africa’s business rescue regime. In exploring these issues, I give a critical review of pertinent literature. With respect to the first issue, I conclude that the legislative provisions granting creditors the right to seek a court order initiating the business rescue process are open to criticism. By contrast, a resolution of the board of directors for the commencement of business rescue is a simpler route. With regard to the second issue I conclude that the company’s creditors have considerable influence in the business rescue process. Overall, the current statutory business rescue regime is intended to give a voice to all major stakeholders in the company’s continued solvent existence. In the event of certain irresoluble disputes in the course of that process, the judiciary has the final say. A substantial number of judicial decisions have provided interpretations of the statutory provisions, and the trend has been to try to restore financial ailing companies to solvency and viability where there is a reasonable prospect for success in this regard. In my conclusion, I propose a legislative model that seeks to strike an optimum balance between the competing and sometimes conflicting interests of the various interested parties and I suggest reforms directed at enhancing the protection of creditors’ rights. This thesis takes account of South African legislation and legislative amendments as at 31 December 2016 and of decisions of the South African courts up to and including those handed down during April 2017 and reported in the saflii on-line law reports. Since a substantial part of this thesis was written from outside South Africa, the author relied heavily on the safllii data base of judgments of the South African courts, rather than on hard copy law reports which take time to reach their destination by post.
Keywords: Financial distress; Liquidation; Rationale for business existence

Banking and financial insolvencies: the European regulatory framework - Parry, Rebecca; Omar, Paul J. (INSOL Europe, 2016)
IRep - Nottingham Trent University's open access institutional research repository
https://irep.ntu.ac.uk/id/eprint/28401/

Teaching and research in international insolvency law: challenges and opportunities - Veder, Michael; Omar, Paul J. (INSOL Europe, 2015)
IRep - Nottingham Trent University's open access institutional research repository
https://irep.ntu.ac.uk/id/eprint/27282/

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

Three Essays on Financial Distress and Corporate Bankruptcy - Chen, Donghui (McMaster University, 2014)
This thesis explores three important issues in financial distress and corporate bankruptcy: bankruptcy venue choice and creditor recovery, the efficiency of Chapter 11 corporate bankruptcy and distressed exchanges, and the bankruptcy ripple effect on peer firms’ investment policy.
Keywords: Bankruptcy; Contagion effect; Corporate Bankruptcy; Distress exchange; Efficiency; Financial distress; Forum shopping; Insolvency

Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Accepted: 2014-02-28T11:57:54Z
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.
URI: https://repository.up.ac.za/handle/2263/53211

Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Nottingham Trent Institutional Repository (IRep) https://core.ac.uk/works/7793942/
Keywords: Cross-border Insolvency; Insolvency; International insolvency

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

A reformatory approach to state regulation of insolvency law in South Africa - Calitz, Juanitta Christelle (University of Pretoria, 2010)
https://repository.up.ac.za/handle/2263/30839
Keywords: Insolvency; South Africa; State regulation

Some comparative aspects of corporate rescue in South African company law - Loubser, Anneli (University of South Africa, 2010)
South African company law has provided for the rescue of financially distressed companies since 1926 when the statutory procedure of judicial management was introduced by the Companies Act 46 of 1926. Unfortunately, judicial management has never been regarded as a successful corporate rescue procedure and for most of its existence it has been severely criticised on many grounds. The Companies Act 61 of 1973 that replaced the Companies Act 46 of 1926 did very little to improve this situation and judicial management remained underutilised. As a result, the Companies Act 71 of 2008 now introduces two newly-created corporate rescue procedures in the form of business rescue proceedings and the compromise with creditors. This study analyses judicial management and the new corporate rescue procedures to establish whether the identified weaknesses of judicial management have been adequately and effectively addressed in the new procedures. A comparative study with similar procedures in England and Germany is undertaken to determine whether the South African legislature has delivered on its promise to create a system of corporate rescue that will meet the needs of a modern South African economy. Several weaknesses in the new procedures are identified and a number of recommendations are made to improve the relevant provisions and to assist in providing South African company law with an efficient and acceptable corporate rescue regime.
https://uir.unisa.ac.za/handle/10500/3575
Keywords: Bankruptcy; Business failures; Business recovery; Business rescue; Corporate insolvency; Corporate reorganizations; Corporate rescue; Corporation law; Debtor and creditor; Financial distress; Insolvency; Insolvency practitioners